Understanding GroEL and DnaK Stress Response Proteins as Antigens for Bacterial Diseases - Kezia R. Fourie; Heather L. Wilson (Vaccines, 2020)
Bacteria do not simply express a constitutive panel of proteins but they instead undergo dynamic changes in their protein repertoire in response to changes in nutritional status and when exposed to different environments. These differentially expressed proteins may be suitable to use for vaccine antigens if they are virulence factors. Immediately upon entry into the host organism, bacteria are exposed to a different environment, which includes changes in temperature, osmotic pressure, pH, etc. Even when an organism has already penetrated the blood or lymphatics and it then enters another organ or a cell, it can respond to these new conditions by increasing the expression of virulence factors to aid in bacterial adherence, invasion, or immune evasion. Stress response proteins such as heat shock proteins and chaperones are some of the proteins that undergo changes in levels of expression and/or changes in cellular localization from the cytosol to the cell surface or the secretome, making them potential immunogens for vaccine development. Herein we highlight literature showing that intracellular chaperone proteins GroEL and DnaK, which were originally identified as playing a role in protein folding, are relocated to the cell surface or are secreted during invasion and therefore may be recognized by the host immune system as antigens. In addition, we highlight literature showcasing the immunomodulation effects these proteins can have on the immune system, also making them potential adjuvants or immunotherapeutics.